Geometry Design-Based Thermoelectric Optimization Module - Aristu Prananca; Iim Fatimah (Jurnal Sains Materi Indonesia, 2023)
One alternative energy source is thermoelectric which is able to convert waste heat into electricity. However, research on thermoelectrics still needs a lot of development, especially module design. Therefore, research on thermoelectric optimization based on the module design was carried out using computer simulation. One of the parameters that can be used for analysis is the maximum output power which is thought to be increased through the cross-sectional area, length, shape, and type of pairs of legs. The principles used in the simulation are about the semiconductor material which is a type of thermoelectric foot material, the Seebeck effect to understand the energy conversion process, resistivity and thermal conductivity to understand the input from the simulation, CaTiO3, and SiC to understand the material used for the model and also Finite Element Analysis. FEA) and output power to understand the processing of simulation results. The research begins by making a design for each variation, entering the specifications, then the running process and calculations to obtain the maximum output power. From the simulation results, it is known that the thermoelectric design will be optimal for small leg lengths, large cross-sectional areas, and using similar materials (Unileg) with good specifications with a maximum output power value of 3,713.10-8 W for beams, 3,634.10-8 W for cylinders, and 8,617.10-8 W For Unileg N-N.